Intersemiotic Transposition: "Crazy about Women", Paul Durcan’s desecrating Art Gallery - Louvel, Liliane (Cadernos de Literatura Comparada, 2021)
I will try to demonstrate in this essay that in the case of Paul Durcan’s art gallery the intersemiotic transposition is seen as inter-course (relation, but also course "entre-deux"), the erotization of the painting by the text, which is shown in Duncan’s iconoclast poems, necessarily written "après/d’après". Maybe also commerce, confrontation between the two - the poem thus becoming the result of this inter-artistic negotiation where who loses, wins.